Peran Kepala Sekolah dalam Peningkatan Kompetensi Pedagogik Guru di SMPN 1 Kedawung - Bagus Nur 'Aliimu; Bambang Sumardjoko; Ari Anshori (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the principal's role in improving teachers' pedagogical competence at SMPN 1 Kedawung. The research aims to analyze how the principal, through various leadership functions, contributes to the development of teachers' pedagogical capabilities. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation. The findings reveal that the principal performs multiple roles including educator, manager, administrator, supervisor, leader, innovator, and motivator. Concrete strategies implemented include weekly briefings, structured training programs, effective use of school operational funds, reflective academic supervision, integration of educational technology, and humanistic leadership practices. These efforts have significantly influenced teachers’ abilities in planning, delivering, and evaluating learning processes. The study underscores the importance of transformational and participatory leadership in fostering sustainable teacher development. The results suggest that strengthening the principal's strategic role can create a more supportive and professional teaching environment, ultimately enhancing the quality of education.